2010
DOI: 10.22230/ijepl.2010v5n10a230
|View full text |Cite
|
Sign up to set email alerts
|

Pass the Crayons: Leadership, Art Production, and Communities of Practice

Abstract: The results of an arts-based leadership (Kelehear, 2006, 2008) practice at a rural middle school in South Carolina are examined. The school principal and art teacher led a day-long staff development and followed up individually to assist teachers to create art as metaphor for individual growth plans as well as school improvement plans. Specifically, the arts-based initiative sought to invite professional conversations that focused on: 1) personal reflections, 2) multiple perspectives, and 3) art making. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The principal as an academic supervisor has the ability to influence teachers to improve their performance. This is in line with Kelehear's opinion that supervisors with skills such as observation skills, analytical skills, data collection skills, counseling and mentoring skills have a better influence on the success of their clients [26]. And Nazer argued a significant relationship between supervisors practices among supervisors and high attitude as the foundation of professional teachers [27].…”
Section: ) Implementation Of Academic Supervisionsupporting
confidence: 68%
“…The principal as an academic supervisor has the ability to influence teachers to improve their performance. This is in line with Kelehear's opinion that supervisors with skills such as observation skills, analytical skills, data collection skills, counseling and mentoring skills have a better influence on the success of their clients [26]. And Nazer argued a significant relationship between supervisors practices among supervisors and high attitude as the foundation of professional teachers [27].…”
Section: ) Implementation Of Academic Supervisionsupporting
confidence: 68%
“…Finally, this study found time to be the greatest stressor and limitation to implementing stress reducing strategies for principals in both nations. Since a principal's stress has been found to negatively impact the school climate (Kelehear, 2004) and unmanaged stress makes a school prone to dysfunction (Darmody and Smyth, 2016), educational leaders must find ways to provide principals with dedicated time to manage the stress of the job. Education leaders of both countries should consider awarding principals a bonus day for each semester to be used at the principal's discretion.…”
Section: Discussionmentioning
confidence: 99%
“…School principals have to manage multiple responsibilities and work under incredibly stressful conditions (Combs et al, 2009;Darmody and Smyth, 2016;Klocko and Wells, 2015;Sogunro, 2012). Kelehear (2004) found that to function effectively, principals must manage their own stress. The findings of this study confirm that principals in Germany and the USA are under stress, identifies causes of their stress, and offers strategies that principals may use to manage their stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation